Efektivitas pertumbuhan Candida albicans pada media alternatif air rebusan kacang kedelai (Glycine max (l) Merr) - Rahmayanti Rahmayanti; Siti Hadijah; Syarifah Wahyuni; Safwan Safwan (Jurnal SAGO Gizi dan Kesehatan, 2022)
Background: Candida albicans are one of the pathogenic fungi in humans whose growth requires carbohydrates and proteins to grow and develop. Soybeans have a reasonably good nutritional content and potential as an alternative medium for the growth of Candida albicans fungi, and soybeans are very easy to find in the community, so they can be used as an alternative medium to replace SGA (Sabouraud Glucose Agar). Soybeans (Glycine max (L.) Merr) have nutritional content consisting of oils, carbohydrates, and minerals that allow them to source nutrients and food for fungi. Furthermore, one of them that can be utilized from soybeans is cooking water.Objectives: The study aims to determine whether soybean (Glycine max (L.) Merr) cooking water media can be an effective alternative for Candida albicans culture.Methods: An analytical study using an experimental design was conducted in the Microbiology laboratory at the Department of Medical Laboratory Technology, Health Polytechnic of Aceh, Ministry of Health, in September 2022. The sample used in this study was soybean cooking water as an alternative medium for Candida albicans. Data collection is based on the culture (breeding) of Candida albicans on alternative media with soybean decoction water as raw material. For the identification of Candida albicans species, confirmation tests were carried out using the germ tube test method. Then the growth assessment of positive (+) colonies of Candida albicans on alternative media of soybean cooking water was incubated for 72 hours (± three days) at 37°C. Data analysis was only done descriptivelyResults: There is the growth of Candida albicans fungal colonies on alternative media from soybean cooking water with macroscopic characteristics of yellowish white color, yeast smell, smooth, smooth surface, flat edges, small colonies, and many colonies. On microscopic observation, Candida albicans fungus was found with microscopic characteristics of round, oval, small, thin-walled, yeast-like cells and pseudohyphae.Conclusion: Soybean (Glycine max (L) Merr) cooking water media is effectively used as an alternative media for the growth of Candida albicans.